The role of rectal redundancy in the pathophysiology of rectal prolapse: a pilot study - AKMERCAN, AHMET; FERATOĞLU, HALE (My University, 2022)
Purpose: Rectal prolapse is hypothesized to be caused due to weakness of the pelvic floor which is related to childbearing. However, half of the female patients with rectal prolapse were reported to be nulliparous and this hypothesis doesn???t explain the prolapse in males. The aim of this study is to evaluate the role of rectal redundancy in rectal prolapse pathophysiology. Methods: This study was conducted prospectively. Fourteen patients who underwent rectopexy were included in the study group. A total of 17 patients who underwent laparotomy for another reason and who have no symptoms regarding rectal prolapse were included in the control group. In order to measure the redundancy of the rectum, we have calculated the ratio of length of intraperitoneal rectum (R) to length of distance between promontorium and peritoneal reflection (PRx). The primary outcome of this study was to evaluate whether the R/PRx ratio is higher in patients with rectal prolapse compared to the control group. Results: Comparing the anatomic features showed that the length of sigmoid colon and length of PRx were not significantly different between the two groups. However, the length of intraperitoneal rectum was significantly higher in the prolapse group. Furthermore, the median R/PRx ratio in the prolapse group was significantly higher than in the control group. Conclusion: This study showed that intraperitoneal rectum in patients with rectal prolapse is significantly more redundant than in the normal population. This could be considered reasonable evidence for the role of rectal redundancy on rectal prolapse pathophysiology. [Ann Surg Treat Res 2022;102(5):289-293]
Keywords: Tıp; Sağlık Bilimleri; Cerrahi Tıp Bilimleri; Medicine; Health Sciences; Surgery Medicine Sciences; CERRAHİ; Klinik Tıp; Klinik Tıp (MED); SURGERY; CLINICAL MEDICINE; Clinical Medicine (MED); Cerrahi; Surgery; Physiopathology; Rectal prolapse; Redundancy; MANAGEMENT